FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHINGSECARA VOLUNTARY (Studi Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2015) - Shartika A. Kencana; Siti Rofingatun; Aaron M. A Simanjuntak (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2018)
This study aims to analyze the factors affecting voluntary auditor displacement at companies listed on the Indonesia Stock Exchange (IDX). The variables used in this research are Change of Management, Financial Distress, Size of Public Accounting Firm, Change Percentage of ROA and Client Size. The population ofthis study are all companies listed on the Indonesia Stock Exchange in the period of2010 to 2015. The number of companies that became sample in this study were 192observation companies obtained by purposive sampling method. Data analysis technique was used logistic regression analysis with SPSS version 16. Based on the analysis, the result shows that thevariable of Management Change, Financial Distress, KAP Size, and Client Size had not affect the size of the sample company to perform auditor switch, while the ROA Percentage Change had significant influence on the sample company to switching auditors